General theory of law: Origins and scope - Vranjanac Dušan (Pravni Zapisi, 2016)
In this article the author deals with the origins of a theoretical legal discipline called General Theory of Law (Allgemeine Rechtslehre) or jurisprudence as it is called in England. After a short historical survey of the development of attempts to theoretical analysis of law, the author analyses works of certain authors considered to be the founders of this discipline (Austin, Merkel, Korkunov). The conclusion is concerned with the importance and scope of this science.